Students’ Perceptions of Technological Tools Used by Teachers in Teaching English during Pandemic Time (Proceedings of English Linguistics and Literature, 2022)
Technological tools were needed to support the online learning in the pandemic time. With so many applications and teaching platforms available, teachers can have certain preferences over them. Similarly, students may prefer a particular teaching platform or technological tool for their learning. Therefore the writers were interested to analyze high school students' perceptions on the use of technological tools by the teachers and how the technological tools help them understand the material. The writers did a qualitative study and used an interview to collect the data. The interview was conducted online with nine students of grade XI of SMKN 4 Pekalongan. The study found that the majority of students held positive perceptions towards their teachers’ use of technological tools. The students felt the use of technological tools was fun and made the learning more effective as the materials were more understandable. It also helped the students access the material at any time. In general, it can be concluded that the students showed a good response on the technological tools used by English teachers. This finding also suggests that the technology has been a great support in the students’ learning during the pandemic time.